O komunikacji twarzą w twarz w perspektywie somatycznej - Laskowski, Wojciech (Investigationes Linguisticae, 2010)
The aim of the article is to present research and theories, which explain why nonverbal behavior, and especially body language, plays the crucial role in regulating communication among people. Firstly, research area will be outlined. An overview of face-to-face communication as a central domain of research in communication studies will be proposed. Secondly, the paper presents the main thesis in human science and in communication studies in particular. According to these thesis body is the main factor of communication process and thus, should be placed in center of the communication research. It means that body regulates what people are intending, feeling, thinking and saying during interaction with other people. It is actually an reversion of verbo-centric approach, which was the most popular and still used in linguistic approach to communication. In order to organize the body-oriented approach, two conceptions will be proposed: sign-symptom distinction and two-channel communication model. The conclusion of this paper is that science of communictation enters a new phase which could be called somatic paradigm.